Emergence: A pluralist approach - Onnis, Erica (THEORIA. An International Journal for Theory, History and Foundations of Science, 2023)
Despite the common use of the concept of emergence, no uncontroversial theoretical framework has been yet formulated in this regard. In this paper, I examine what this circumstance suggests about the significance and usefulness of this concept. I first trace a brief history of the notion of emergence from its first formulation among the British Emergentists to its contemporary uses. Then, I outline its most common features and examine three examples of emergent phenomena, namely particle decay, free will, and division of labour in ant colonies. These three cases of emergence exhibit different features and imply criteria which only partially overlap. I then suggest that the multiplicity of features and criteria recognised as defining emergence, rather than being a threat to the tenability of the concept, should encourage the assumption of a pluralist attitude that is consistent with both the employment of this idea in different sciences and the recognition of emergent phenomena across different levels of organisation. Finally, I propose that emergence can be approached in a similar way to how Richard Boyd approached the problem of natural kinds, namely by identifying an open cluster of properties, rather than a set of necessary and sufficient conditions.